Longitudinal associations between allostatic load, pet ownership, and socioeconomic position among U.S. adults aged 50+ - Jennifer W. Applebaum; Shelby E. McDonald; Barbara A. Zsembik (Elsevier, 2023)
It is hypothesized that pets provide benefits to human health by buffering the deleterious effects of stress, but varying exposure to chronic stress via social position is rarely considered in these conceptual and empirical models. Allostatic load is an index of biological and physical measures that represents cumulative wear and tear on the body via chronic stress exposure. In this study, we use the 2006-2016 waves of the Health and Retirement Study, a nationally representative, longitudinal panel survey of adults aged 50+ in the United States, to test whether and to what extent pet ownership has an impact on allostatic load, and whether pet ownership moderates the effects of socioeconomic position on allostatic load. Linear mixed effects regression models revealed that pet owners had significantly lower allostatic load scores than those who do not own pets; however, after adjusting for socioeconomic position (i.e., wealth, education, race, ethnicity, gender, marital status), the effect of pet ownership was no longer significant. We estimated a series of models stratified by sociodemographic groups to test moderation effects. Among those who had a high school education, pet owners had lower allostatic load scores, whereas among those who had attended some college, pet owners had higher scores. Among those who were aged 80+, pet owners had higher scores than those who did not own pets. These findings suggest that the magnitude of the effect of pet ownership on allostatic load may not be sufficient to counteract experiences of high chronic stress as experienced by lower-status groups. Supporting the human-animal bond may contribute to improving older adult population health if paired with efforts to address the underlying causes of population health disparities.